Intervention for promoting breast milk use in neonatal intensive care unit: a pilot study. (March 2014) - Giannì, Maria Lorella; Roggero, Paola; Amato, Orsola; Orsi, Anna; Garbarino, Francesca; Garavaglia, Elisa; Poletti, Barbara; Plevani, Laura; Mosca, Fabio
Abstract Objective: The health benefits provided by breast milk are significant in preterm infants. Despite recommendations, rates of breastfeeding in preterm infants are lower than in term infants. The aim of this study was to evaluate the efficacy of a multidisciplinary intervention in promoting any breastfeeding in preterm infants at discharge. Methods: A prospective non-randomized interventional cohort study was conducted. One hundred and twenty-two preterm infants constituted the historical group. A multidisciplinary intervention was performed including staff training and setting up and implementation of a written breastfeeding procedure. Results: One hundred and ten preterm infants were enrolled in the intervention group. The percentage of infants fed human milk at discharge was 69 and 62 in the intervention group and in the historical group, respectively. The percentage change from any breastfeeding at full enteral feeding attainment to formula feeding at discharge was lower in the intervention group than in the historical group (−9 versus −23). Belonging to the intervention group and having at least one stress factor during pregnancy were independently associated with any breast milk feeding at discharge. Conclusions: The multidisciplinary intervention performed appears to be effective in promoting any breastfeeding in preterm infants at discharge.